Lung Tumor Cell-Derived Exosomes Promote M2 Macrophage Polarization - Pritchard, Alexandra (Cells, 2020)
Cellular cross-talk within the tumor microenvironment (TME) by exosomes is known to promote tumor progression. Tumor promoting macrophages with an M2 phenotype are suppressors of anti-tumor immunity. However, the impact of tumor-derived exosomes in modulating macrophage polarization in the lung TME is largely unknown. Herein, we investigated if lung tumor-derived exosomes alter transcriptional and bioenergetic signatures of M0 macrophages and polarize them to an M2 phenotype. The concentration of exosomes produced by p53 null H358 lung tumor cells was significantly reduced compared to A549 (p53 wild-type) lung tumor cells, consistent with p53-mediated regulation of exosome production. In co-culture studies, M0 macrophages internalized tumor-derived exosomes, and differentiated into M2 phenotype. Importantly, we demonstrate that tumor-derived exosomes enhance the oxygen consumption rate of macrophages, altering their bioenergetic state consistent with that of M2 macrophages. In vitro co-cultures of M0 macrophages with H358 exosomes demonstrated that exosome-induced M2 polarization may be p53 independent. Murine bone marrow cells and bone marrow-derived myeloid-derived suppressor cells (MDSCs) co-cultured with lewis lung carcinoma (LLC)-derived exosomes differentiated to M2 macrophages. Collectively, these studies provide evidence for a novel role for lung tumor-exosomes in M2 macrophage polarization, which then offers new therapeutic targets for immunotherapy of lung cancer.